Detection of a nonerythropoietic erythropoietin, Neuro‐EPO, in blood after intranasal administration in rat. Issue 11 (9th September 2020) - Martin, Laurent; Garcia Rodriguez, Julio Cesar; Audran, Michel; Ericsson, Magnus; Maurice, Tangui; Marchand, Alexandre
Abstract: Nonerythropoietic erythropoietins (EPOs) are investigated for their high antioxidant properties. A new drug candidate under clinical investigation to treat brain diseases is Neuro‐EPO, produced by selecting EPO isoforms with low sialic acid content. Intranasal administration allows to bypass the blood–brain barrier to get a fast and concentrated delivery to the brain. The aims of this project were to characterize Neuro‐EPO with anti‐doping methods used to detect conventional recombinant EPOs (isoelectric focusing [IEF] and sodium dodecyl sulfate–polyacrylamide gel electrophoresis [SDS‐PAGE]) and to evaluate the window of detection of Neuro‐EPO in brain and blood (plasma) after a single intranasal administration in rats. Neuro‐EPO drug analyzed by IEF‐PAGE presented a very basic profile completely detected only when using a 2–8 or 2–10 pH gradient instead of the conventional 2–6 pH gradient. Its profile consisted in six main bands that did not interfere with endogenous EPO profile from human or rat. After SDS‐PAGE, a broad band was detected for Neuro‐EPO in the same area as endogenous EPO, making Neuro‐EPO identification very difficult by this approach. Therefore, IEF was the method for identification chosen after administration in rats. Neuro‐EPO was clearly identified in blood 2 and 6 h after the delivery. Fainter signals were obtained between 12 and 48 h, but some characteristic very basic bands remained detectable. Surprisingly, brain extracts did not show the presence of Neuro‐EPO even 2 h after administration, indicating a fast degradation or elimination from the brain to the bloodstream. This experiment indicated that detection of Neuro‐EPO after intranasal delivery should be possible for a few days. Abstract : Neuro‐EPO is a new nonerythropoietic drug investigated to treat brain diseases. Neuro‐EPO migrates in the same area as endogenous EPO by SDS‐PAGE. Neuro‐EPO can be identified by IEF using a 2–10 pH gradient. Neuro‐EPO can be detected in plasma from 2 to 48‐h post‐intranasal administration.